The ART of life: IVF or child adoption? - Gulcin Gumus; Jungmin Lee (Institute for the Study of Labor (IZA), 2010)
This paper analyzes the effects of child adoption on the utilization of assisted reproductive technology (ART) in the US. Using state-level longitudinal data for 1999-2006, we show that ART use is responsive to changes in adoption markets. Controlling for state-specific fixed effects, the estimated elasticity of ART cycles performed with respect to child adoptions is about -0.13 to -0.15. The responsiveness is higher when we consider infant adoptions, adoptions by older women, and international adoptions while there is no substitutability between ART and adoption of related children. Our findings suggest that public policies regarding adoption, including subsidies, influence ART use.
Keywords: I11; J13; J18; 330; Child adoption; infertility treatment; assisted reproductive technology (ART); in vitro fertilization (IVF); Familienrecht; Fruchtbarkeit; Krankheit; Gesundheitsversorgung; USA